2016
DOI: 10.1128/jvi.01369-16
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of Iridovirus, Polyomavirus, and a Unique Member of a New Group of Fish Papillomaviruses in Lymphocystis Disease-Affected Gilthead Sea Bream

Abstract: Lymphocystis disease is a geographically widespread disease affecting more than 150 different species of marine and freshwater fish. The disease, provoked by the iridovirus lymphocystis disease virus (LCDV), is characterized by the appearance of papillomalike lesions on the skin of affected animals that usually self-resolve over time. Development of the disease is usually associated with several environmental factors and, more frequently, with stress conditions provoked by the intensive culture conditions pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 54 publications
(55 reference statements)
0
80
0
2
Order By: Relevance
“…In contrast, only 39 ruminant PV types are recognized up to now (https://pave.niaid.nih.gov/), which leads us to support the importance of improving the efforts to characterize animal PVs. Recent studies, some using high‐throughput sequencing platforms have shown that animal PVs were underestimated and new types have been characterized (Bauermann et al., ; Da Silva et al., ; Daudt, da Silva, Streck, et al., ; López‐Bueno et al., ; Tore et al., ).…”
Section: Papillomaviruses Species In Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, only 39 ruminant PV types are recognized up to now (https://pave.niaid.nih.gov/), which leads us to support the importance of improving the efforts to characterize animal PVs. Recent studies, some using high‐throughput sequencing platforms have shown that animal PVs were underestimated and new types have been characterized (Bauermann et al., ; Da Silva et al., ; Daudt, da Silva, Streck, et al., ; López‐Bueno et al., ; Tore et al., ).…”
Section: Papillomaviruses Species In Ruminantsmentioning
confidence: 99%
“…Papillomaviruses (PVs) have been associated with cutaneous and mucosal warts, and neoplasia in a variety of animal species (Borzacchiello & Roperto, ; Rector & Van Ranst, ). Members of this viral family are described in a diversity of mammal genera, but they have also been described in birds, reptiles and fish, and probably infect all amniotes (López‐Bueno et al., ; Rector & Van Ranst, ). PVs are strictly species‐ and tissue‐specific although some established (Lunardi, Alfieri, et al., ; Lunardi, De Alcântara, et al., ; Nasir & Campo, ) and unusual cross‐infections have been reported (Munday, Hanlon, Howe, Squires, & French, ).…”
Section: Introductionmentioning
confidence: 99%
“…Individual types have been shown to be highly species and tissue specific. To date, papillomaviruses have been described in fish (16), reptiles (17,18), birds (19) and mammals (20). Based on the suggestion that papillomaviruses have coevolved with their hosts (21), it appears that papillomaviruses have been an evolutionary success for over 500 million years.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this case a papilloma-and a polyomavirus were also detected in the same specimen, their complete genome sequences were recovered, providing the first description of a papillomavirus in fish. Moreover, the genome of the sequenced iridovirus (termed as LCDV-Sa) proved to be much longer (the largest known vertebrate iridovirus genome) then the formerly described LCDVs, thus LCDV-Sa should be considered a novel and distinct virus species within the genus Lymphocystivirus (Lopez-Bueno et al, 2016).…”
Section: Discovery Of Novel Virusesmentioning
confidence: 99%